Sesbania rostrata - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Sesbania rostrata : proceedings of an intemational colloquium, 184pp ISBN 92 908 1 0890